An Autopsy Case of Spontaneous Coronary Artery Dissection With Eosinophilic Coronary Periarteritis and Degeneration of Medial Smooth Muscles. (December 2021) - Fukuta, Mamiko; Kurose, Akira; Horita, Tetsuya; Otaki, Jun; Nakamura, Yoshimi; Kanno, Sanae; Kato, Hideaki; Aoki, Yasuhiro
Abstract : Abstract: A 45-year-old woman with no known medical history died suddenly shortly after complaining of anterior chest discomfort. The autopsy revealed a dissection at the anterior descending branch of the left coronary artery, and eosinophilic adventitial inflammation was observed both in the right coronary artery and in the vicinity of the dissection. Furthermore, there was degeneration of the tunica media in the right coronary artery, and this was thought to be a predissection lesion. In the degenerated area of the tunica media, probable apoptosis of smooth muscle cells was noted, suggesting that the degeneration was not due only to the effect of eosinophilic lytic enzymes. These findings also indicated that eosinophilic infiltration preceded the dissection. Eosinophilic infiltration around the coronary arteries is occasionally observed in cases of sudden death, but although it might be associated with the death, the pathological mechanism is yet to be elucidated. Eosinophilic periarteritis has also been observed around the site of spontaneous coronary artery dissection, although a causal relationship is unproven. The histopathology of this case indicated that the eosinophilic infiltration preceded the dissection. Detailed pathological findings are presented, together with a review of the literature.